Healthcare Technology Self-Efficacy (HTSE) and its influence on individual attitude: An empirical study. (May 2016) - Rahman, Mohammed Sajedur; Ko, Myung; Warren, John; Carpenter, Darrell
Abstract: Previous research on technology acceptance and adoption has established perceived self-efficacy as an important factor influencing user acceptance of information technologies. However, research on self-efficacy perceptions and its effect on user attitude in the context of health technologies is limited. This study identifies three self-efficacy factors that may be important for shaping individual attitude toward healthcare technologies. This research proposes a new context-specific self-efficacy factor, Healthcare Technology Self-Efficacy (HTSE) and a conceptual model incorporating HTSE and two existing self-efficacy factors, General Self-Efficacy (GSE) and Computer Self-Efficacy (CSE). The conceptual model is validated using a survey of 314 participants. We found that HTSE has a positive influence on attitude toward the use of health technologies. We also found that two existing self-efficacy constructs (GSE and CSE) have positive relationships with HTSE. However these two factors did not have any significant influence on attitude toward health technology use, contrary to our expectations. Rather, HTSE mediates the relationships between GSE and attitude and the relationship between CSE and attitude in the context of health technology use behavior. The results of this study have important implications for both research and practice in the healthcare technology domain. Highlights: New context-specific factor 'Healthcare Technology Self-Efficacy (HTSE)' is proposed. Relationships between existing self-efficacy factors (GSE, CSE) and HTSE were tested. GSE and CSE have positive relationships with HTSE. HTSE positively influence individuals' attitudes toward healthcare technology use. HTSE also mediates the relationships between GSE and attitudes and CSE and attitudes.